Use of Animation in Simplifying the Learning of Abstract Concepts of History and Government in Secondary Schools in Kenya - Munene, Kanyi Christopher (Machakos University Press, 2021)
Students’ diverse learning abilities render the need to develop various learning materials for effective learning. Existing literature has shown the increasing use of real-life and documentary videos and teaching aids to complement classroom teaching. While there are studies on effectiveness of documentary videos in existing literature, relatively little is reported on use of animation videos in teaching History and Government in comparison to traditional written text in terms of their impact on learning outcomes in secondary schools in Kenya. In response to this, this study sought to examine the role of animation in simplifying the teaching of abstract concepts of History and Government in Secondary Schools in Kenya and the impact that animation has had on comprehension and learner retention of war-related concepts. The study adopted a qualitative research model that relied on document analysis, observation and oral interviews to collect data. A sample of 179 History and Government learners was engaged and divided into two groups. One group was exposed to animated videos based on content taught in three subtopics while the other did not watch these videos. Thereafter, a written and oral examination was administered to both groups. The group that had watched animated content performed better than the latter. The second group later watched animated content and was examined. Its performance became better than the first group. These results imply that that animated video can effectively complement text materials. It is recommended that the KICD in collaboration with the TSC should further improve existing learning materials by developing animated content based on the Kenyan syllabus and make the content freely available online.
Keywords: Animation; Learning; Comprehend; Abstract; Recall; Secondary school; History